Institutional Constraints in Promoting IK : Community Access to Social Networks and Formal Institutions - World Bank (Washington, DC, 2012)
In recent years, many international development agencies and non-government organizations have renewed their efforts to provide and promote indigenous knowledge orientation in development planning and practice. These efforts emphasize local knowledge systems and practices as valuable resources in global development. The four distinct aspects of indigenous knowledge oriented development interventions frequently debated are: Documentation: indigenous knowledge documentation, communication and adaptation; Ownership: local ownership of specific knowledge practices; Reward System: rewarding local knowledge innovations (through documentation and dissemination, cross-region recognition, global application and value addition); and Access to Knowledge and Institutions: linking modern and indigenous institutions for sustainable development and enhancing local community access to markets, government agencies, financial institutions, university based research centers and international development publications. This study of local innovators in India reflects on the IK aspects outlined above, but emphasize the institutional access dimension in promoting innovative local approaches. Clearly, there are likely to be more similarities than differences between what is described here and the situation in other developing countries of the South.